2000
DOI: 10.1046/j.1442-9071.2000.00249.x
|View full text |Cite
|
Sign up to set email alerts
|

Secondary haemorrhage after dacryocystorhinostomy

Abstract: Secondary haemorrhage after DCR was found to occur after 3.8% of DCR. Risk factors include being immunocompromised and taking NSAID prior to surgery. The haemorrhage did not adversely affect surgical outcome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
10
1

Year Published

2003
2003
2013
2013

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 16 publications
2
10
1
Order By: Relevance
“…This gives a rate of less than 3% which compares well with both previous endonasal studies 21 and external DCR studies. 22 There were no cases of orbital fat exposure or frontal sinusitis which can occur if the dissection is taken too posteriorly into the uncinate. 21 Damage to the orbital plate of the ethmoid (lamina papyracea) and frontonasal duct can occur if the dissection is taken too posterior.…”
Section: Resultsmentioning
confidence: 94%
“…This gives a rate of less than 3% which compares well with both previous endonasal studies 21 and external DCR studies. 22 There were no cases of orbital fat exposure or frontal sinusitis which can occur if the dissection is taken too posteriorly into the uncinate. 21 Damage to the orbital plate of the ethmoid (lamina papyracea) and frontonasal duct can occur if the dissection is taken too posterior.…”
Section: Resultsmentioning
confidence: 94%
“…1991; Hanna et al. 1998; Tsirbas & McNab 2002). A study conducted on 112 patients between the ages of 70 and 90 reported no serious complications following external DCR (Hurwitz et al.…”
Section: Discussionmentioning
confidence: 99%
“…Dacryocystorhinostomy on an outpatient basis is generally accepted as a safe procedure. Nausea and epistaxis were the most frequent complications that prompted patients to present to the hospital, and various studies have reported the incidence of such complications as 0.5-4.0% (Dresner et al 1991;Hanna et al 1998;Tsirbas & McNab 2002). A study conducted on 112 patients between the ages of 70 and 90 reported no serious complications following external DCR (Hurwitz et al 2000).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Various studies displayed 0.5-3.9% secondary hemorrhage in cases with DCR. 4,10,[14][15][16] In cases with excessive intraoperative bleeding, a nasal tampon may be used to avoid postoperative hemorrhage.…”
Section: Discussionmentioning
confidence: 99%